All-solid-state battery

By adding a specific proportion of Sn, Mg and Ag metal phases to the first solid electrolyte layer of the all-solid battery, the problem of insufficient short-circuit suppression in the all-solid battery is solved, and higher battery performance and safety are achieved.

CN119833730APending Publication Date: 2025-04-15TOYOTA JIDOSHA KK
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202410932329.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-10-13
Filing Date
2024-07-12
Publication Date
2025-04-15

AI Technical Summary

Technical Problem

In an all-solid battery using the precipitation and dissolution reaction of metal lithium as the negative electrode reaction, there is a problem of insufficient short circuit suppression.

Method used

By adding a solid electrolyte containing metal phases such as Sn, Mg, and Ag to the first solid electrolyte layer of the all-solid battery, the proportion of the metal phase is controlled to be less than 2.50 volume % to suppress the occurrence of short circuit.

Benefits of technology

It effectively suppresses the occurrence of short circuits, and improves the cycle characteristics and charging capacity of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119833730A_ABST
    Figure CN119833730A_ABST
Patent Text Reader

Abstract

The invention relates to an all-solid-state battery. The present invention relates to an all-solid-state battery having, in order in the thickness direction, a negative electrode current collector, a first solid electrolyte layer, a second solid electrolyte layer, and a positive electrode active material layer using a precipitation / dissolution reaction of lithium metal as a negative electrode reaction, the first solid electrolyte layer containing: a solid electrolyte phase containing a first solid electrolyte; and a metal phase containing at least one of Sn, Mg and Ag, the proportion of the metal phase in the first solid electrolyte layer is 2.50 vol% or less, and the second solid electrolyte layer contains a second solid electrolyte and does not contain the metal phase.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present disclosure relates to all-solid-state batteries. Background Art

[0002] All-solid batteries generally have a solid electrolyte layer between a positive electrode active material layer and a negative electrode active material layer. In addition, in the field of batteries, batteries that utilize the precipitation and dissolution reaction of metallic lithium as a negative electrode reaction are known.

[0003] For example, Japanese Patent Application Laid-Open No. 2021-089814 discloses an all-solid-state battery that utilizes the precipitation-dissolution reaction of metallic lithium as the reaction of the negative electrode, and the battery has a negative electrode collector, a Li absorption layer, a metal M layer, a solid electrolyte layer, and a positive electrode layer in sequence. Summary of the invention

[0004] The all-solid-state battery using the precipitation and dissolution reaction of metallic lithium as the negative electrode reaction has the advantages of being easy to simplify the manufacturing process and easily improving the energy density. This is because, usually, when making such an all-solid-state battery, a conventional negative electrode active material layer (a layer containing negative electrode active material particles that absorb and release Li) is not provided, but the negative electrode active material layer (Li-containing layer) is formed by initial charging. On the other hand, in the all-solid-state battery using the precipitation and dissolution reaction of metallic lithium as the negative electrode reaction, there is still room for further improvement in short circuit suppression.

[0005] The present disclosure has been made in view of the above-mentioned actual situation, and a main object of the present disclosure is to provide an all-solid-state battery with suppressed short circuit.

[0006] Solution 1

[0007] A fully solid-state battery, which utilizes the precipitation and dissolution reaction of metallic lithium as a negative electrode reaction, and has a negative electrode collector, a first solid electrolyte layer, a second solid electrolyte layer and a positive electrode active material layer in sequence in the thickness direction, wherein the first solid electrolyte layer contains: a solid electrolyte phase containing a first solid electrolyte; and a metal phase containing at least one of Sn, Mg and Ag, wherein the proportion of the metal phase in the first solid electrolyte layer is less than 2.50% by volume, and the second solid electrolyte layer contains a second solid electrolyte and does not contain the metal phase.

[0008] Solution 2

[0009] The all-solid-state battery according to claim 1, wherein the ratio of the metal phase in the first solid electrolyte layer is 0.10% by volume or more.

[0010] Solution 3

[0011] The all-solid-state battery according to Option 1 or Option 2, wherein the first solid electrolyte and the second solid electrolyte are sulfide solid electrolytes.

[0012] Solution 4

[0013] The all-solid-state battery according to any one of Schemes 1 to 3, wherein the metal phase contains at least Sn.

[0014] Solution 5

[0015] An all-solid-state battery according to any one of Schemes 1 to 4, wherein the all-solid-state battery has a metal layer between the negative electrode collector and the first solid electrolyte layer, and the metal layer has a Mg layer and a Sn layer in order from the negative electrode collector side.

[0016] The present disclosure achieves the effect of being able to provide an all-solid-state battery in which short circuits are suppressed. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] Features, advantages, and technical and industrial significance of exemplary embodiments of the present invention will be described below with reference to the accompanying drawings, wherein like reference numerals represent like elements, and wherein:

[0018] Figure 1 This is a schematic cross-sectional view illustrating an all-solid-state battery of the present disclosure. DETAILED DESCRIPTION

[0019] The all-solid-state battery of the present disclosure will be described in detail below using the accompanying drawings. The following drawings are schematic representations, and the size and shape of each part are exaggerated as appropriate for easier understanding.

[0020] Figure 1 This is a schematic cross-sectional view illustrating an all-solid-state battery of the present disclosure. Figure 1 The all-solid-state battery 10 shown in FIG. T The negative electrode current collector 1, the metal layer 2, the first solid electrolyte layer 3A, the second solid electrolyte layer 3B, the positive electrode active material layer 4 and the positive electrode current collector 5 are sequentially provided. The first solid electrolyte layer 3A contains: a solid electrolyte phase containing a first solid electrolyte; and a metal phase containing at least one of Sn, Mg and Ag. In addition, in the first solid electrolyte layer 3A, the proportion of the above-mentioned metal phase is 2.50 volume % or less. In addition, the second solid electrolyte layer 3B contains a second solid electrolyte and does not contain the above-mentioned metal phase.

[0021] According to the present disclosure, in a battery utilizing the precipitation-dissolution reaction of metallic lithium as a negative electrode reaction, the first solid electrolyte layer contains a predetermined metal phase at a predetermined ratio, thereby achieving an all-solid-state battery in which the occurrence of a short circuit is suppressed.

[0022] Sn, Mg and Ag contained in the metal phase are all metals that can be alloyed with Li. Therefore, it is speculated that by using such a metal, dendrites can be captured and the occurrence of short circuits can be suppressed. In addition, it is speculated that the contact area between the metal phase dispersed in the first solid electrolyte layer and the first solid electrolyte is high, so the generation of the starting point of the dendrite can be suppressed. In addition, when the all-solid-state battery is charged, an alloy of the above-mentioned metal and Li is generated in the first solid electrolyte layer, and the generated alloy functions as a protective layer that protects the decomposition of the sulfide solid electrolyte. As a result, the cycle characteristics can be improved. On the other hand, it is speculated that if the proportion of the above-mentioned metal is too much, micro short circuits are likely to occur.

[0023] In addition, in the all-solid battery disclosed herein, the first solid electrolyte layer on the negative electrode side contains a solid electrolyte phase and a metal phase, thereby increasing the area of ​​contact between the solid electrolyte and the metal on the negative electrode side. As a result, it becomes an all-solid battery with good input characteristics (charging capacity).

[0024] 1. Negative electrode collector

[0025] Examples of the material of the negative electrode current collector include SUS, copper, nickel, and carbon. Examples of the shape of the negative electrode current collector include a foil shape. The thickness of the negative electrode current collector is, for example, 1 μm or more and 500 μm or less.

[0026] 2. First solid electrolyte layer

[0027] The first solid electrolyte layer contains at least a first solid electrolyte. In addition, the first solid electrolyte layer in the present disclosure contains a predetermined metal phase at a predetermined ratio.

[0028] The metal phase contains at least one of Sn, Mg and Ag. The metal phase may contain only one of Sn, Mg and Ag, or may contain two or more. The metal phase preferably contains at least Sn. In the metal phase, Sn, Mg and Ag may each exist as a single substance, or may exist as an alloy. As alloys, Li-Sn alloys, Li-Mg alloys, and Li-Ag alloys may be listed.

[0029] In the first solid electrolyte layer, the ratio of the above-mentioned metal phase is 2.50 volume % or less, can be 2.44 volume % or less, can be 2.00 volume % or less, can be 1.50 volume % or less. On the other hand, the ratio of the above-mentioned metal phase is, for example, 0.05 volume % or more, can be 0.10 volume % or more, can be 0.12 volume % or more, can be 0.20 volume % or more, can be 0.50 volume % or more. The ratio of the metal phase can be calculated, for example, by element mapping using scanning electron microscope energy dispersive X-ray spectroscopy (SEM-EDX).

[0030] In the first solid electrolyte layer, usually, the above-mentioned metal phase exists dispersedly. In addition, the first solid electrolyte layer may be an island structure with a solid electrolyte phase containing the first solid electrolyte as a sea and a metal phase as an island. Furthermore, the solid electrolyte phase may contain a binder described later in addition to the first solid electrolyte. The average size (average diameter) of the metal phase is, for example, less than 10 μm, less than 5 μm, less than 3 μm, or less than 1 μm. On the other hand, the size of the metal phase is, for example, more than 0.01 μm.

[0031] In addition, the first solid electrolyte layer contains a first solid electrolyte. As the first solid electrolyte, for example, inorganic solid electrolytes such as sulfide solid electrolytes, oxide solid electrolytes, and halide solid electrolytes; organic solid electrolytes such as polymer electrolytes and gel electrolytes can be listed. The sulfide solid electrolyte preferably contains sulfur (S) as the main component of the anion element. The oxide solid electrolyte preferably contains oxygen (O) as the main component of the anion element. The halide solid electrolyte preferably contains a halogen (X) as the main component of the anion. Among these, a sulfide solid electrolyte is preferred.

[0032] The sulfide solid electrolyte may be a glass-based (amorphous) sulfide solid electrolyte, a glass-ceramic sulfide solid electrolyte, or a crystalline sulfide solid electrolyte. Examples of the crystal phase contained in the sulfide solid electrolyte include an LGPS crystal phase, a Thio-LISICON crystal phase, and an Argentum-based crystal phase.

[0033] Examples of sulfide solid electrolytes include Li 2 SP 2 S 5 , Li 2 SP 2 S 5 -LiI, Li 2 SP 2 S 5 -GeS 2 , Li 2 SP 2 S 5 -Li 2 O. Li 2 SP 2 S 5 -Li 2 O-LiI、Li 2 SP 2 S 5 -LiI-LiBr, Li 2 S-SiS 2 , Li 2 S-SiS 2 -LiI, Li2 S-SiS 2 -LiBr, Li 2 S-SiS 2 -LiCl, Li 2 S-SiS 2 -B 2 S 3 -LiI, Li 2 S-SiS 2 -P 2 S 5 -LiI, Li 2 SB 2 S 3 , Li 2 SP 2 S 5 -Z m S n (wherein m and n are positive numbers, and Z is any one of Ge, Zn, and Ga.) Other examples of sulfide solid electrolytes include Li 2 S-GeS 2 , Li 2 S-SiS 2 -Li 3 PO 4 , Li 2 S-SiS 2 -Li x MO y (wherein x and y are positive numbers, and M is any one of P, Si, Ge, B, Al, Ga, and In).

[0034] The first solid electrolyte layer may contain a binder. As a binder, for example, a rubber-based binder such as butene rubber (BR), styrene butadiene rubber (SBR), and a fluoride-based binder such as polyvinylidene fluoride (PVDF) can be listed. In addition, the thickness of the first solid electrolyte layer is, for example, 1 μm or more, 10 μm or more, or 15 μm or more. On the other hand, the thickness of the first solid electrolyte layer is, for example, 100 μm or less, or 50 μm or less. As a method for forming the first solid electrolyte layer, for example, a method of injecting a metal (giving a metal) into the solid electrolyte layer before pressing by sputtering can be listed. There is no particular limitation on the maximum value of the distance (the distance in the thickness direction) from the reference plane to the metal phase with the surface on the negative electrode collector side of the first solid electrolyte layer as the reference plane, for example, it is 1 μm or more, 3 μm or more, or 5 μm or more.

[0035] 3. Second solid electrolyte layer

[0036] The second solid electrolyte layer is a layer containing a second solid electrolyte and not containing the above-mentioned metal phase. It can be confirmed by element mapping using SEM-EDX that the second solid electrolyte layer does not contain a metal phase.

[0037] In addition, the second solid electrolyte layer usually contains a second solid electrolyte and may further contain a binder. For the second solid electrolyte, it is the same as the first solid electrolyte described in "2. First solid electrolyte layer". In addition, for the binder, it is the same as the content described in "2. First solid electrolyte layer". In addition, the second solid electrolyte layer and the first solid electrolyte layer are preferably configured in a directly connected manner. In this case, it is preferred that there is an interface between the first solid electrolyte layer and the second solid electrolyte layer.

[0038] 4. Positive electrode active material layer

[0039] The positive electrode active material layer contains at least a positive electrode active material. In addition, the positive electrode active material layer may contain at least one of a solid electrolyte, a conductive material, and a binder.

[0040] Examples of the positive electrode active material include oxide active materials. Examples of the oxide active material include LiCoO 2 、LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O 2 Rock salt layered active materials, LiMn 2 O 4 , Li 4 Ti 5 O 12 Spinel active materials, LiFePO 4 Olivine-type active materials such as the positive electrode active material. The shape of the positive electrode active material may be, for example, a particle shape. The average particle size (D 50 ) is, for example, 0.5 μm or more and 50 μm or less. The average particle size (D 50 ) refers to the volume cumulative particle size measured using a laser diffraction scattering particle size distribution measuring device.

[0041] As the conductive material, for example, a carbon material can be cited. As the carbon material, for example, acetylene black (AB) and Ketjen black (KB) and other particulate carbon materials; carbon fiber, carbon nanotube (CNT) and carbon nanofiber (CNF) and other fibrous carbon materials can be cited. For the solid electrolyte and the binder, the contents are the same as those described in "2. First solid electrolyte layer". The thickness of the positive electrode active material layer is, for example, not less than 1 μm and not more than 500 μm.

[0042] 5. All-solid-state batteries

[0043] The all-solid-state battery may have a metal layer between the negative electrode current collector and the first solid electrolyte layer. The metal layer is a layer composed of at least one of a metal single substance and an alloy. As the metal, there is no particular limitation as long as it is a metal that can be alloyed with Li, and preferably contains at least Mg.

[0044] The metal layer is, for example, a thin film, preferably a vapor-deposited film. The thickness of the metal layer is not particularly limited, for example, it is 30 nm or more. On the other hand, the thickness of the metal layer may be, for example, 2000 nm or less, or 1500 nm or less. In addition, the metal layer may be formed by a vapor deposition method such as vacuum vapor deposition.

[0045] The metal layer may contain no Li or may contain Li. The former is equivalent to the state of the metal layer in the all-solid battery before the initial charge, and the latter is equivalent to the state of the metal layer in the all-solid battery after the initial charge. When Li is introduced into the metal layer by the initial charge, the metal contained in the metal layer is alloyed with Li. As a result, an alloy phase such as Mg-Li alloy phase is formed in the metal layer. On the other hand, during discharge, Li moves from the metal layer alloyed with Li to the positive electrode side. In addition, a Li phase can be formed inside the metal layer. In addition, a precipitated Li layer can be formed between the metal layer and the first solid electrolyte layer. In addition, a precipitated Li layer can be formed between the metal layer and the negative electrode collector.

[0046] In addition, the metal layer may be a single layer or a layer formed by stacking multiple layers. In the former case, the metal layer is preferably a layer composed of at least one of Mg metal (Mg single substance) and Mg alloy (alloy with Mg as the main component), i.e., the so-called Mg layer. In the latter case, it is preferred to have the above-mentioned Mg layer and Sn layer, and the above-mentioned Sn layer is arranged on the surface on the opposite side of the surface on the negative electrode collector side of the above-mentioned Mg layer. That is, the metal layer preferably has a Mg layer and a Sn layer in sequence from the negative electrode collector side. Furthermore, the Sn layer is composed of at least one of Sn metal (Sn single substance) and Sn alloy (alloy with Sn as the main component).

[0047] The all-solid-state battery disclosed herein generally has a positive electrode collector for collecting electrons of the positive electrode active material layer. Examples of materials for the positive electrode collector include SUS, aluminum, nickel, and carbon. Examples of shapes for the positive electrode collector include foil. Examples of thicknesses for the positive electrode collector include 1 μm or more and 500 μm or less.

[0048] In addition, the all-solid battery of the present disclosure may have an outer package that houses the above-mentioned members. Examples of the outer package include a laminated outer package and a shell-type outer package.

[0049] There is no particular limitation on the use of the all-solid-state battery, for example, the power supply of the vehicle can be cited. That is, in the present disclosure, a vehicle equipped with the above-mentioned all-solid-state battery can also be provided. As a vehicle, for example, a hybrid electric vehicle (HEV), a plug-in hybrid electric vehicle (PHEV), a battery electric vehicle (BEV), a gasoline vehicle, and a diesel vehicle can be cited. In particular, the all-solid-state battery of the present disclosure is preferably used for a driving power supply of a hybrid electric vehicle (HEV), a plug-in hybrid electric vehicle (PHEV) or a battery electric vehicle (BEV). In addition, the all-solid-state battery can be used as a power supply for a mobile body (such as a railway, a ship, an aircraft) other than a vehicle, and can be used as a power supply for electrical products such as an information processing device.

[0050] The present disclosure is not limited to the above-mentioned embodiments. The above-mentioned embodiments are illustrative only, and any technical solution having substantially the same structure and achieving the same effect as the technical concept described in the patent claims of the present disclosure is included in the technical scope of the present disclosure.

[0051] Example 1

[0052] Preparation of positive electrode

[0053] The positive electrode active material, solid electrolyte, conductive material, binder and dispersion medium were added to a polypropylene (PP) container and stirred for 30 seconds using an ultrasonic dispersion device. The positive electrode active material was NCA active material. The solid electrolyte was LiI containing 2 SP 2 S 5 It is a sulfide solid electrolyte. The conductive material is vapor grown carbon fiber (VGCF). The binder is a butyl butyrate solution containing 5% by weight of PVDF. The dispersion medium is butyl butyrate. The ultrasonic dispersion device is UH-50 made by SMT. In addition, the amount of positive electrode active material and solid electrolyte is expressed as a volume ratio of 75:25. Secondly, the PP container was vibrated with a vibrator (TTM-1 made by Shibata Science Co., Ltd.) for 30 minutes. Thus, a positive electrode slurry was obtained. Using a coater, the positive electrode slurry was applied to the positive electrode collector (Al foil) by a doctor blade method and dried naturally. Then, it was dried on a hot plate at 100°C for 30 minutes. Thus, a positive electrode having a positive electrode collector and a positive electrode active material layer was obtained.

[0054] Fabrication of negative electrode collector

[0055] Mg was deposited on the surface of the negative electrode current collector (Ni foil) to form a Mg layer (thickness 1000 nm). Thus, a negative electrode current collector having a Mg layer was prepared.

[0056] Fabrication of electrolyte layer components

[0057] The solid electrolyte, binder and dispersion medium were added to a container and stirred for 30 seconds using an ultrasonic dispersing device. The solid electrolyte was LiI-containing 2 SP 2 S 5 It is a sulfide solid electrolyte. The binder is a heptane solution containing 5% by weight of PVDF. The dispersion medium is heptane. The ultrasonic dispersion device is UH-50 manufactured by SMT. Secondly, the container was vibrated with a vibrator (TTM-1 manufactured by Shibata Science Co., Ltd.) for 30 minutes. In this way, a solid electrolyte slurry was obtained. Using a coater, the solid electrolyte slurry was applied to a substrate (PET film) by a scraper method and dried naturally. Thus, two components having a solid electrolyte layer on a substrate were prepared. For one solid electrolyte layer, Sn was sputtered in such a way that the volume ratio of Sn became 0.12% by volume, thereby obtaining a first solid electrolyte layer. The components were bonded in such a way that the first solid electrolyte layer was opposite to the other solid electrolyte layer (the second solid electrolyte layer), and the components were pressed with 7 tons / cm 2 After pressing, the PET film was peeled off. Furthermore, Sn was vapor-deposited on the surface of the first solid electrolyte layer to form a Sn layer (thickness 100 nm). Thus, an electrolyte layer member having a Sn layer, a first solid electrolyte layer and a second solid electrolyte layer was obtained.

[0058] Preparation of evaluation batteries

[0059] The above-mentioned negative electrode collector and the above-mentioned electrolyte layer member are punched out into Φ14.5mm respectively. The negative electrode collector and the electrolyte layer member are overlapped in a manner that the Mg layer is opposite to the Sn layer. Then, the positive electrode punched out into Φ11.28mm is overlapped in a manner that the positive electrode active material layer is opposite to the second solid electrolyte layer to obtain a stack. The positive terminal and the negative terminal are connected to the stack, clamped with a laminate film, welded, and sealed. For the sealed stack, cold isostatic pressing (CIP) is used to apply a pressure of 392MPa. Then, it is constrained with a metal plate at a pressure of 1MPa. In this way, a battery for evaluation is produced.

[0060] Comparative Example 1

[0061] In the production of the electrolyte layer member, an electrolyte layer member and an evaluation cell were produced in the same manner as in Example 1, except that Sn was not sputtered on the solid electrolyte layer before pressing.

[0062] Examples 2 to 4 and Comparative Example 2

[0063] An evaluation battery was produced in the same manner as in Example 1, except that an electrolyte layer member was produced so that the ratio of Sn in the first solid electrolyte layer became the volume ratio shown in Table 1.

[0064] evaluate

[0065] Cross-section SEM observation

[0066] The evaluation cells obtained in Examples 1 to 4 and Comparative Example 2 were operated at 60°C in CCCV mode at 0.15 mA / cm 2 (0.03mA / cm 2 The charged battery was disassembled and cross-sectioned, and the dispersion state of Sn in the first solid electrolyte layer was confirmed by SEM-EDX.

[0067] From the results of SEM-EDX, it was found that Sn was dispersed in the first solid electrolyte layer in all the evaluation cells.

[0068] Evaluation of input characteristics

[0069] Each of the obtained evaluation batteries was heated at 25°C, 3.0 V to 4.2 V, and 3 mA / cm 2 CC charging was performed under the conditions of , and the obtained charging capacity was measured. In addition, the presence or absence of short circuit was confirmed. The results are shown in Table 1.

[0070] Table 1

[0071] Sn ratio (volume %) Whether there is a short circuit Charging capacity (mAh) Comparative Example 1 0 have - Example 1 0.12 none 1.88 Example 2 0.25 none 1.91 Example 3 0.50 none 1.75 Example 4 2.44 none 1.55 Comparative Example 2 4.76 have -

[0072] As shown in Table 1, in Comparative Examples 1 and 2, short circuits occurred and the charge capacity could not be measured. On the other hand, in Examples 1 to 4, short circuits did not occur and the charge capacity was also good. This confirmed that in the all-solid-state battery disclosed in the present invention, the occurrence of short circuits was suppressed and the charge capacity was also good.

Claims

1. A fully solid-state battery, which utilizes the precipitation and dissolution reaction of metallic lithium as a negative electrode reaction, and has a negative electrode collector, a first solid electrolyte layer, a second solid electrolyte layer and a positive electrode active material layer in the thickness direction, The first solid electrolyte layer contains: a solid electrolyte phase containing a first solid electrolyte; and a metal phase containing at least one of Sn, Mg and Ag, The ratio of the metal phase in the first solid electrolyte layer is 2.50 volume % or less, The second solid electrolyte layer contains a second solid electrolyte and does not contain the metal phase.

2. The all-solid-state battery according to claim 1, wherein: The ratio of the metal phase in the first solid electrolyte layer is 0.10 volume % or more.

3. The all-solid-state battery according to claim 1, wherein: The first solid electrolyte and the second solid electrolyte are sulfide solid electrolytes.

4. The all-solid-state battery according to claim 1, wherein: The metal phase contains at least Sn.

5. The all-solid-state battery according to any one of claims 1 to 4, wherein The all-solid-state battery includes a metal layer between the negative electrode current collector and the first solid electrolyte layer, the metal layer including a Mg layer and a Sn layer in order from the negative electrode current collector side.

Citation Information

Patent Citations

  • All-solid battery

    JP2021089814A